(untitled) (Al Basirah, 2022)
Ma’rūf bin Abdul al-Ghanī al-Russāfi was a great Arabic poet and writer. As a great advocate of freedom he opposed his contemporary rulers of Irāq. He was known as a poet of freedom. After serving at various indigenous Educational Institutions, he started work as lecture at the Royal College Istanbul as lecturer, after the fall of the Ottoman Empire, he left Istanbul and travelled to Syria as the British authorities in Irāq. He settled in Damascus for one year. He returned to Irāq and started a newspaper: Al-Amal. He joined the committee for translation as its vice chairman. He became an inspector in the directorate of Education. He became a professor at Higher Teachers institution in end of third decade of nineteenth century. Ma’rūf Al-Rassāfī served his country as a social worker. He was acquainted with western literature through translation and his writing career while he was in Istanbul. He wrote poetry in four chapters and this article is about his poetry entitled: An artistic study of the poetry of Maruf Al-Rasafi . His Arabic poetry is full of elements of rhetoric, as he uses similes metaphors, illusions, hints and other rhetorical phenomena. His Arabic poetry is full with new trends especially social and political trends. We tried to elaborate these trends with examples from his poetry. He uses new vocabulary style and terms in his poetry, we have tried our best to present all these elements from his Arabic poetry in this article. We have tried to present its contribution to Arabic poetry in Modern period. We tried to present its status among its contemporary scholars. The article describes a best collection of his rhetorical phenomena in his Arabic poetry. Keywords: Rhetoric, Poetry, Trends, Social Values, Irāq, Maruf Rusāfī.